2015
DOI: 10.1073/pnas.1420419112
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell SIRT1–HIF1α axis programs the differentiation of CD4 + T cells through IL-12 and TGF-β1

Abstract: The differentiation of naive CD4+ T cells into distinct lineages plays critical roles in mediating adaptive immunity or maintaining immune tolerance. In addition to being a first line of defense, the innate immune system also actively instructs adaptive immunity through antigen presentation and immunoregulatory cytokine production. Here we found that sirtuin 1 (SIRT1), a type III histone deacetylase, plays an essential role in mediating proinflammatory signaling in dendritic cells (DCs), consequentially modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
103
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(122 citation statements)
references
References 68 publications
8
103
1
2
Order By: Relevance
“…The lack of SIRT1 in DCs reduced critical cytokine production, including IFNβ and IL-12, which we suggest contributed to a pathological Th2/Th17 immune response within the airways. Previous studies examining DC-specific KO mice reported no changes in DC maturation, differentiation, or development compared to WT DCs (39, 40), in agreement with our observations. Thus, our data indicate that SIRT1 has a unique role in modulating DC cytokine production in the context of a viral infection, such as RSV (12).…”
Section: Discussionsupporting
confidence: 93%
“…The lack of SIRT1 in DCs reduced critical cytokine production, including IFNβ and IL-12, which we suggest contributed to a pathological Th2/Th17 immune response within the airways. Previous studies examining DC-specific KO mice reported no changes in DC maturation, differentiation, or development compared to WT DCs (39, 40), in agreement with our observations. Thus, our data indicate that SIRT1 has a unique role in modulating DC cytokine production in the context of a viral infection, such as RSV (12).…”
Section: Discussionsupporting
confidence: 93%
“…ϩ differentiation toward Th1-like T cells (59). Again, these experiments must be performed in a tumoral context to gain insights into the consequences of HIF-1 stabilization in DCs in CD4 ϩ T cell differentiation.…”
Section: Hypoxia Potentiates Treg Cell Immunosuppressive Functionmentioning
confidence: 99%
“…Indeed, the blockade of glycolysis inhibits Th17 cell generation while stimulating Foxp3+ Treg cell development [66]. Finally, HIF-1α signaling in antigen presenting cells has been shown to modulate their ability to promote the differentiation of Th1 cells and Foxp3+ Tregs [70]. Collectively, these findings suggest that, besides its direct role in cancer cell metabolism, HIF-1α is an important factor in the control of tumor-specific immunity.…”
Section: Hif-1αmentioning
confidence: 99%